(untitled) (Research, Society and Development, 2022)
The increasingly intense competition allied to the growing demand from customers has made it essential for companies to adopt the concepts and tools of business logistics. In the retail sector, this condition is even more imperative in specific areas of logistics management, such as the management of storage and material handling, decisively contributing to obtaining a competitive advantage over competitors that do not apply such concepts and tools. This article aims to carry out a systematic literature review on the role of the distribution center (DC) in the supermarket sector. 64 published studies on the subject were analyzed. The logistical functions that make up the operations of a DC were identified in the literature and discussed, providing a greater understanding of the processes, allowing the continuous improvement of these activities. The results demonstrate the importance of logistics activities linked to DCs, especially for the supermarket sector. This research can contribute to logistics professionals who are seeking a better understanding of DC management activities and flows.